2010
DOI: 10.1016/j.amjcard.2009.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Blockade With Anakinra to Prevent Adverse Cardiac Remodeling After Acute Myocardial Infarction (Virginia Commonwealth University Anakinra Remodeling Trial [VCU-ART] Pilot Study)

Abstract: Acute myocardial infarction (AMI) initiates an intense inflammatory response in which interleukin-1 (IL-1) plays a central role. The IL-1 receptor antagonist is a naturally occurring antagonist, and anakinra is the recombinant form used to treat inflammatory diseases. The aim of the present pilot study was to test the safety and effects of IL-1 blockade with anakinra on left ventricular (LV) remodeling after AMI. Ten patients with ST-segment elevation AMI were randomized to either anakinra 100 mg/day subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
222
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 357 publications
(248 citation statements)
references
References 27 publications
15
222
0
7
Order By: Relevance
“…The pathogenetic processes in bleomycin-induced fibrosis are simply a model for IPF and results cannot be extrapolated to human IPF. However, in patients with acute myocardial infarction, there is evidence that IL-1 blockade with IL-1Ra suppresses the inflammatory response and positively affects tissue remodelling [24].…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
“…The pathogenetic processes in bleomycin-induced fibrosis are simply a model for IPF and results cannot be extrapolated to human IPF. However, in patients with acute myocardial infarction, there is evidence that IL-1 blockade with IL-1Ra suppresses the inflammatory response and positively affects tissue remodelling [24].…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
“…We have recently reported that, in patients with STEMI, anakinra significantly blunted the acute systemic response measured as leukocyte count and CRP levels (8,9). Here we describe the effects of anakinra on leukocyte activity.…”
Section: Discussionmentioning
confidence: 96%
“…However, only recently has IL-1 emerged as a novel target for intervention in heart disease (7). The initial experience with anakinra, the recombinant form of the naturally occurring human IL-1 receptor antagonist, in patients with ST-segment elevation myocardial infarction (STEMI) suggests that IL-1 blockade blunts the acute systemic inflammatory response, since leukocyte counts and plasma C-reactive protein (CRP) levels were reduced, as well as the incidence of heart failure (8,9). Yet, the effects of anakinra on leukocyte activity in patients with STEMI remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale clinical trials have also sought to evaluate the effect of IL-1 inhibition on inflammation and cardiac remodelling in stable-STEMI and non-STEMI patients [155,156], reporting that IL-1 inhibition reduced post-MI inflammation but had little effect on cardiac function in the longer term. This may relate to the relatively mild inflammatory phenotype in these patient cohorts compared with less stable STEMI patients, in which IL-1 blockade was more effective [157]. Further studies in patients with more severe MI are likely to be required to evaluate the true potential of IL-1 inhibition as an effective therapy for post-MI morbidity and mortality.…”
Section: Therapeutic Approaches To Target Damp Pathwaysmentioning
confidence: 97%